Do antihypertensive drugs really have antitumor effects? Baseline differences in hypertensive and non-hypertensive patients with advanced pancreatic cancer. Issue 29 (22nd July 2022) - Iede, Kiyotsugu; Yamada, Terumasa; Ueda, Masami; Tsuda, Yujiro; Nakashima, Shinsuke; Ohta, Katsuya; Tanida, Tsukasa; Matsuyama, Jin; Ikenaga, Masakazu; Tominaga, Shusei
Abstract : Although the antitumor effects of antihypertensive drugs for patients with advanced pancreatic cancer (APC) have been investigated, their efficacy remains unclear. Previous studies suggest that hypertensive (HT) patients with APC are significantly older than non-HT patients with APC, and that other major baseline differences in patient characteristics which may affect prognosis exist between HT and non-HT patients. It is also possible that antihypertensive drugs lack antitumor activity. Therefore, we herein retrospectively investigated the baseline differences between HT and non-HT patients with APC. From January 2015 to April 2020, 56 patients with APC received nab-paclitaxel plus gemcitabine as first-line chemotherapy at Higashiosaka City Medical Center (Higashiosaka, Japan). Of these 56 patients, 30 were diagnosed with hypertension (HT group); the remaining 26 did not have hypertension (non-HT group). Differences between the two groups were compared and prognostic factors were evaluated. Patients in the HT group had significantly less sarcopenia, a significantly larger body mass index, were significantly older, and significantly more likely to have a regular doctor and primary site in the body and tail of the pancreas than those in the non-HT group. Although no significant difference was found in the treatment response, patients in the HT group were significantly more likely to move to second-line chemotherapy than those in the non-HT group. Survival curves showed that median overall survival (OS) in the HT group was significantly longer (10.5 months) than in the non-HT group (6.8 months, P = .04). Multivariate analysis did not identify the use of antihypertensive drugs as an independent prognostic factor of OS. We identified key baseline differences in the characteristics of APC patients with and without HT, suggesting that major selection bias could occur when investigating the efficacy of antihypertensive drugs in all populations. Therefore, it is possible that antihypertensive drugs lack antitumor activity. To determine the true efficacy of antihypertensive drugs for APC, HT, and non-HT patients in another population should be investigated, or a prospective, randomized, controlled trial conducted that is stratified by HT or non-HT status.